Russia and the West: Clash of energy interests through the lens of realist and liberal approaches - Yu. V. Borovsky (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
By the beginning of the 2010s, the powerful positive impetus inherent to the Russia-Western relations in the energy sector has waned. Substantial disagreements arose on all major issues of the agenda, from the views on the prospects for the Russian fuel and energy complex development and participation of foreign capital in it, to the implementation of concrete gas transportation projects and to assessments of opportunities for legal and institutional regulation of energy relations in Europe and the world. The Russian military operation in Ukraine in 2022 has greatly exacerbated all these tensions, rendering virtually impossible any form of cooperation in the energy sector. These circumstances raise questions about the driving forces, ideological imperatives, and the very logic of the energy policy development both in Russia and the West. The present paper compares two different interpretations of these issues based on insights from the realist and liberal theoretical frameworks. The first section highlights basic theoretical and methodological premises of these approaches in general and outlines their potential application to the energy issues in particular. Then the author assesses the explanatory potential of each of these approaches with regard to the key issues in relations between Russia and the West in the energy sector. The author admits that many steps taken by Russia, as well as the US and the EU can be well explained from the viewpoint of liberal approach (e.g. attempts of some EU countries to depoliticize energy cooperation with Russia or the EU measures to prevent monopolization of its energy market by Gazprom). However, political realism provides a more compelling explanation of previous dynamics of international relations in this field, their current state and prospects. The policy of energy transition, implemented by Western countries to lower their carbon dependence, fits particularly well the logic of the realist approach, although potential tensions between Russia and the West in that regard have not yet fully materialized.